Efek Kecemasan Sosial pada Pengobatan Penyakit Behçet - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Milna Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Behçet's disease is a multisystem inflammatory disorder that can significantly impact patients' quality of life. This study conducts a meta-analysis aimed at elucidating the effects of social anxiety on treatment outcomes for Behçet's disease through a comprehensive synthesis of existing literature. Initially, a systematic search was performed across major electronic databases to identify relevant studies published between 2014 and 2024. Out of 1,253 initially identified articles, 18 studies met the inclusion criteria, encompassing 2,487 Behçet's disease patients. The meta-analysis revealed a significant negative correlation between social anxiety levels and treatment adherence for Behçet's disease (r = -0.42, p < 0.001), which was positively associated with disease symptom severity (g = 0.58, 95% CI [0.41, 0.75]). Moderator analysis indicated that the effect of social anxiety on Behçet's treatment outcomes was more pronounced in patients with mucocutaneous manifestations (Q = 7.23, p = 0.007). Additionally, social anxiety showed a strong negative correlation with patients' quality of life in health (r = -0.53, p < 0.001), with the most substantial impact observed in the social functioning domain. Furthermore, thematic analysis of the potential mechanisms underlying the relationship between anxiety and Behçet's treatment outcomes confirmed the mediating roles of patient-doctor communication barriers, increased stigma perception, and avoidance behaviour. These findings underscore the importance of assessing and addressing social anxiety in the comprehensive management of Behçet's disease. The researchers suggest that these findings could have implications for improving patient treatment and quality of life. Finally, the study supports the integration of targeted psychological interventions into standard care protocols for Behçet's disease and emphasizes the need for a biopsychosocial approach to managing this condition.